Análise econômica e histórica do instituto da unitização - Monteiro, William Luiz de Souza (2010)
This paper deals with the theme 'The Institute of Unitization,' or even 'Individualization of Production,' as national classification, terms that describe what happens to be a joint and coordinated from a reservoir of oil or gas by all parties with property rights on the areas where the reservoir stretches. The concepts of Unitization will be studied and discussed according to context of the oil industry in its entirety technical, legal and economic issues. In light of Economic Theory, will be analyzed the Fundamentals of the Institute of Unitization and evolution of its application in national and international context.